PASSING AS A FORM OF ADAPTATION: THE ISLAMIC NUANCES OF THE CHRISTIANS AND CATHOLICS - Riza Saputra (Khazanah: Jurnal Studi Islam dan Humaniora, 2019)
This study aims to discuss the phenomenon of the Christians and Catholics that imitate Islamic expressions in Banarjoyo village. The cordial relationship among Muslims, the Christians and Catholics of Banarjoyo village provide new nuances on the concept of passing. Using field research and collecting data through participant observation and in-depth semi structured interview techniques, the study reaches the following results: Christians and Catholics adaptation with Muslims activities in Banarjoyo village undergirds on three aspects of social interaction, namely parallel, associative, and cooperative. The processes of Christians and Catholics’ interaction and participation within Muslims activities are the causes of the identification, and imitation of Islamic expressions. The main factor of the Christians and Catholics imitation of Islamic expression is because of their role identity and their feeling dissimilar that further make them try to assimilate with the dominant Islamic context. This assimilation and adjustment of Christians and Catholics behaviors as well as Muslims is what we called as “Passing as a form of adaptation.”